Internal displacement in Kenya: the quest for durable solutions - Kiama, L; Koome, F (Refugee Studies Centre, University of Oxford, 2014)
Internal displacement in Kenya has been a challenge since the colonial era but only recently has a legal framework been developed to address IDP protection issues. The process of developing this framework offers some useful lessons for stakeholders in similar situations.